Determination of lethal concentration and antibacterial activity of commonly used disinfectants - Alam, M; Rahman, MM; Foysal, MJ; Hossain, MN (International Journal of Natural Sciences, 2012)
The toxic effects of four disinfectants viz., copper sulfate (CuSO4), potassium permanganate (KMnO4), methylene blue and malachite green on fish and fish pathogenic bacteria Aeromonas sp., Pseudomonas fluorescens, Edwardsiella sp. and Flavobacterium sp. were investigated. Lethal concentration of the disinfectants to fingerlings of Labeo rohita was determined in aquarium by standard method. Lethal concentration of copper sulfate (CuSO4), potassium permanganate (KMnO4), methylene blue and malachite green against fish were found in 0.75ppm, 7ppm, 6ppm and 0.5ppm at 21.4hrs, 18hrs, 9.5hrs and 1.40hrs, respectively. Methylene blue at 4ppm and 5ppm concentration inhibited the growth of Pseudomonas fluorescens and 6ppm concentration suppressed the growth of Aeromonas sp. Copper sulfate (CuSO4) was effective only against Edwardsiella sp at concentration of 10ppm and 8ppm. Malachite green repressed the growth of all four tasted bacteria at a concentration of 1ppm. Potassium permanganate (KMnO4) was failed to exhibit any inhibitory effect on the bacteria even at 30ppm concentration. DOI: http://dx.doi.org/10.3329/ijns.v1i4.9738 IJNS 2011 1(4): 102-105